Climate Change Adaptation in Europe and Central Asia : Disaster Risk Management - Kryspin-Watson, Jolanta; Pollner, John; Nieuwejaar, Sonja (World Bank, Washington, DC, 2017)
The following paper serves as a sectoral background note for the regional report ‘managing Uncertainty: Adapting to Climate Change in Europe and Central Asia Countries’. It focuses on what is known about the implications of climate change for extreme weather and the ability of Europe and Central Asia (ECA) to mitigate and manage the impact of extreme events. It also explains how climate change will increase weather-induced disasters in ECA, highlighting the sensitivity of ECA’s population to these hazards, and recommending various measures in the area of financial and fiscal policy, disaster risk mitigation, and emergency preparedness and management, to reduce current and future vulnerabilities. The goals of this paper are to: (i) present forecasts on how climate change will affect weather-related hazards and secondary effects, and what impact the extreme hydro-meteorological phenomena will have on the countries of Europe and Central Asia; and (ii) provide an overview of measures to mitigate and manage these risks.